Análisis del índice de competitividad regional de Loreto en comparación con las otras regiones del Perú periodo 2019 – 2022 - Chong Ríos, Germán Vladimir (2025)
The Regional Competitiveness Index is a tool used to measure the competitiveness of regions through six pillars, which together are determined by 40 indicators. This tool was used to analyze the different competitive aspects of Loreto and its position compared to other regions in the country. The Lima region is divided into Metropolitan Lima and El Callao as one region, and Lima Provinces as another; therefore, 25 regions are analyzed. The main purpose is to analyze the competitiveness of Loreto during the 2019–2022 period, for which this descriptive, quantitative, non-experimental study is developed. The central conclusion shows that Loreto is the least competitive region in the country, ranking 25th. That is, in last place, with a score of 3 on a scale of 0 to 10. Despite all this, the analysis of the indicators places Institutions as the most competitive in Loreto, with an average score of 5.55 points over the four years, placing it in 10th place out of 25 regions. In contrast, the least competitive indicator in Loreto is Education, with an average score of 1.35 points, relegating it to 25th place compared to the other regions. The Health indicator is also very low at 1.73 points, placing Loreto in 25th place. The most competitive aspects of Loreto are: perception of regional public management, gender income gap, and road network.